A global climatological study of the ionospheric foF2 and hmF2 covariance - Danielle Edwards; Manuel Cervera; Bruce Ward; Andrew MacKinnon (Advances in Space Research, 2026)

Novel perturbation approach for inferring equatorial ionospheric vertical E× Bdrift velocity using ground-based magnetometers - Tristan Camilleri; Manuel Cervera; Bruce Ward; Andrew MacKinnon (Advances in Space Research, 2026)

Dietary Analysis of Commercial Fish (Families Mullidae and Sparidae) from Bay of Cádiz, Southern Spain: An Integrative Approach - José Manuel Guerra-García; Sandra Calero-Cano; Pablo Arechavala-Lopez; Juan Lucas Cervera-Currado; Iñigo Donázar-Aramendía (Fishes, 2025)
A combination of stomach contents analysis (SCA) and nitrogen (δ15N) and carbon (δ13C) stable isotope analysis (SIA) was used to assess the trophic structure of nine fish species (two belonging to the family Mullidae, Mullus barbatus and Mullus surmuletus, and seven belonging to the family Sparidae, Diplodus sargus, Diplodus vulgaris, Pagellus acarne, Pagellus erythrinus, Pagrus auriga, Pagrus pagrus, and Sparus aurata) with high commercial value in the Bay of Cádiz, Southern Spain. A total of 91 different food items were identified in the stomachs, mainly belonging to four animal phyla (Arthropoda, Mollusca, Annelida, and Echinodermata). Crustaceans (primarily decapods and amphipods) were the most common prey consumed by the species of Mullus, Pagrus, and Pagellus, whereas macroalgae, polychaetes, and molluscs were dominant in D. sargus, D. vulgaris, and S. aurata stomachs, respectively. Diet composition and isotopic signature differed among fish species, indicating food partitioning among coexisting species. Some discrepancies appeared when comparing fish trophic level using SCA versus SIA, since SCA provides information on recently consumed items, while SIA generates data about source utilization over a period of several months. Integration of both approaches offers a more comprehensive understanding of feeding strategies. Dietary studies shed light on the trophic ecology of commercial fish species, being the baseline for future ecological modelling and long-term management of marine resources.

Origin and Biogeography of the Colourful Sap‐Sucking Sea Slugs Genus Thuridilla Bergh, 1872 (Mollusca, Gastropoda, Heterobranchia) - M. Rosario Martín‐Hervás; Leila Carmona; Patrick J. Krug; Terence Gosliner; J. Lucas Cervera; Manuel António E. Malaquias (Journal of Biogeography, 2025)
Aim Thuridilla Bergh, 1872, is a lineage of herbivorous sea slugs externally distinguished by bright colours and distinctive patterns of lines and spots. Recent work revealed an exceptionally rapid, cryptic radiation of 13 species in the Indo‐Pacific, raising questions about mechanisms of speciation in this group. Here, we (i) study the diversification and historical biogeography of Thuridilla in a phylogenetic context and (ii) assess the role of dispersal and vicariance as the predominant mode of speciation in the genus. Location Tropical and temperate regions of the Atlantic and Indo‐Pacific. Major Taxa Studies Gastropoda, Sacoglossa. Methods A nearly complete taxon set with 28 out of 32 recognised species of Thuridilla was used, in a total sample of 172 specimens, together with sacoglossan outgroups. Phylogenetic relationships were determined using a multi‐locus approach combining two mitochondrial (COI and 16S) and one nuclear gene (H3). Species relationships, diversification times, and ancestral geographical ranges were inferred using relaxed‐clock methods together with Bayesian discrete phylogeographic methods under three calibration scenarios using the oldest known fossil of Sacoglossa, Berthelinia elegans Crosse, 1875, and tectonic events. Results Thuridilla species branched off into four major clades in all calibration scenarios: two groups from the Atlantic plus Indo‐West Pacific (5 and 6 species) and two clades from the Indo‐West Pacific (4 and 17 species). The highest diversity of the genus is in the Western Pacific (14 spp.) with a peak in the East Indies Triangle (18 spp.), whereas the Atlantic is depauperate with only four species occurring in this ocean basin. Divergence between Atlantic and Indo‐West Pacific lineages occurred in two main temporal periods: the Miocene and the Pliocene. Speciation events within the 13 cryptic species‐complex fell mostly within Plio‐Pleistocene times. Main Conclusions The best supported hypothesis was an Indo‐West Pacific origin of Thuridilla between 28 and 18 Mya during the Early Miocene. In the western Pacific, speciation likely occurred during transient allopatry during Plio‐Pleistocene sea‐level fluctuations. Under the three tested calibration scenarios, the limited diversity of the Atlantic Ocean is hypothesized to be derived from Miocene vicariant events associated with the closure of the Tethys Sea, dispersal across southern Africa, or long‐distance dispersal across the East Pacific Barrier prior to the uplift of the Isthmus of Panama. Thuridilla is absent in the Eastern Pacific, potentially resulting from the extinction of ancestral lineages following the uplift of the Isthmus of Panama. Near‐complete sampling of diversity and reconstruction of historical biogeography thus yielded new insight into the relative contributions of dispersal versus vicariance during speciation over the history of this widely distributed, colourful genus.

The Heterobranchia gastropods from the Cabo Verde Islands (NE Atlantic): A hot-spot of endemism - Manuel António E. Malaquias; Martina Turani; Evandro Lopes; Juan L. Cervera (Regional Studies in Marine Science, 2025)

CLIMF2: A climatological model of the ionospheric F2 layer. Part 1: Model methodology - Danielle J. Edwards; Thomas E. Chambers; Manuel A. Cervera (Advances in Space Research, 2025)

CLIMF2: A climatological model of the ionospheric F2 layer. Part 2: Validation and comparison with IRI - Danielle J. Edwards; Thomas E. Chambers; Manuel A. Cervera (Advances in Space Research, 2025)

Unraveling the shifts in the belowground microbiota and metabolome of Pinus pinaster trees affected by forest decline - Ana V. Lasa; Miriam López-Hinojosa; Pablo J. Villadas; Antonio José Fernández-González; María Teresa Cervera; Manuel Fernández-López (Science of The Total Environment, 2025)

The FOODRUS index: Assessing suitability for effective food loss and waste prevention management under an integral perspective - Manuel Amador-Cervera; Juan S. Angarita-Zapata; Alberto de la Calle Vicente; Ainhoa Alonso-Vicario (Waste Management, 2024)

An intelligent mushroom strain selection model based on their quality characteristics - Jorge Cervera-Gascó; José E. Pardo; Manuel Álvarez-Ortí; Eulogio López-Mata; Diego Cunha Zied; Arturo Pardo-Giménez (Food Bioscience, 2023)

A Spanish dancer? No! A troupe of dancers: a review of the family Hexabranchidae Bergh, 1891 (Gastropoda, Heterobranchia, Nudibranchia) - Yara Tibiriçá; Marta Pola; Cory Pittman; Terrence M. Gosliner; Manuel A. Malaquias; Juan Lucas Cervera (Organisms Diversity & Evolution, 2023)
Color ontogeny and variations associated with discrete morphological differences may generate taxonomical challenges, which requires multiple data types and in-depth historical review. The nudibranch known as the Spanish dancer, Hexabranchus sanguineus , is a classic example with over 200 years of taxonomic confusion. Currently, H. sanguineus is accepted by most authors as a single species from the Indo-Pacific Ocean with Hexabranchus morsomus as a valid species from the Atlantic Ocean. Yet, despite these species being highly studied, their systematic status remains debatable. Over 30 synonyms have been proposed for H. sanguineus and even a distinct genus for H. morsomus . Here we provide, for the first time, a comprehensive review of all proposed names and an integrative taxonomic revision of the genus including morphological and molecular data. Our results reveal that H. sanguineus is a complex of five species: four previously described and an undescribed species, one of the largest nudibranchs in the world: Hexabranchus giganteus sp. nov. The genus Caribranchus is considered a junior synonym of Hexabranchus Ehrenberg, 1828 and the ontogeny of color pattern is discussed.

Development of the POLIVAR model using neural networks as a tool to predict and identify monovarietal olive oils - Jorge Cervera-Gascó; Adrián Rabadán; Eulogio López-Mata; Manuel Álvarez-Ortí; José E. Pardo (Food Control, 2023)

Short-term impact of spent coffee grounds over soil organic matter composition and stability in two contrasted Mediterranean agricultural soils - Francisco Comino; Ana Cervera-Mata; Victor Aranda; Juan Manuel Martín-García; Gabriel Delgado (Journal of Soils and Sediments, 2020)

Assessing the effect of high doses of ampicillin on five marine and freshwater phytoplankton species: a biodegradation perspective - Beatriz Baselga-Cervera; Manuel Cordoba-Diaz; Camino García-Balboa; Eduardo Costas; Victoria López-Rodas; Damian Cordoba-Diaz (Journal of Applied Phycology, 2019)

Towards a standardized methodology for monitoring and assessing marine mobile epibenthic communities across spatio-temporal scales - Macarena Ros; Víctor López De La Rosa; Triana Revanales; Andrea Spinelli; Alejandro Fernández-Romero; Lucas Cervera-Currado; Jose Manuel Guerra-García (Frontiers in Marine Science, 2019)

Safety and efficacy of daptomycin in outpatient parenteral antimicrobial therapy: a prospective and multicenter cohort study (DAPTODOM trial) - Carlos Cervera; Pedro Sanroma; Víctor González-Ramallo; Cristina García de la María; Gemma Sanclemente; Nieves Sopena; Marcos Pajarón; Antonio Segado; Manuel Mirón; Francisco Antón; Andima Basterretxea; Ana Cuende; et al. (Infectious Diseases, 2017)

Ontogenetic changes in the spicule formation and their possible role in chromodorid opisthobranchs (Mollusca, Chromodorididae) - Luis Sánchez-Tocino; J. Manuel Tierno de Figueroa; Juan Lucas Cervera (Marine Biology Research, 2014)

Hydroid assemblages across the A tlantic– M editerranean boundary: is the S trait of G ibraltar a marine ecotone? - Manuel M. González‐Duarte; Cesar Megina; Stefano Piraino; Juan L. Cervera (Marine Ecology, 2013)
Strong gradients in physico‐chemical properties between abutting water masses create prominent transition zones in the marine environment. The S trait of G ibraltar forms the well defined boundary between the M editerranean and A tlantic, and this paper examines spatial variation of hydroid assemblages in this transition zone. Although several studies highlighted the transitional character of the Strait and defined it as an ecotone, the benthic hydroid assemblages did not show differences between the G ulf of C ádiz and the A lboran S ea. However, there is an asymmetrical influence of the Atlantic waters on the coastal benthic ecosystems of the A lboran S ea, which maintains a more Mediterranean character in the hydroid assemblages of the northern coast, whereas a more A tlantic character was found in the rest of the studied sites. The transition zone between A tlantic and M editerranean benthic communities could be associated with an A tlantic I nfluence Z one rather than with the S trait of G ibraltar itself.

Theta synchronization between the hippocampus and the nucleus incertus in urethane-anesthetized rats - Ana Cervera-Ferri; Juan Guerrero-Martínez; Manuel Bataller-Mompeán; Alida Taberner-Cortes; Joana Martínez-Ricós; Amparo Ruiz-Torner; Vicent Teruel-Martí (Experimental Brain Research, 2011)